2005
DOI: 10.1061/(asce)1090-0241(2005)131:6(740)
|View full text |Cite
|
Sign up to set email alerts
|

Geosynthetic Clay Liner Interaction with Leachate: Correlation between Permeability, Microstructure, and Surface Chemistry

Abstract: International audienceWhen a geosynthetic clay liner (GCL) containing sodium bentonite is brought into contact with fluids containing other cations, the latter may exchange with the sodium present between clay layers. This modification of clay surface chemistry may change the clay microstructure and hence its hydraulic conductivity. The influence of clay surface chemistry on microstructure and permeability, after prolonged contact between two GCLs (a natural sodium bentonite GCL and a sodium-activated calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 20 publications
3
39
0
1
Order By: Relevance
“…Isomorphic substitution in montmorillonite usually results in the replacement of a portion of tetravalent silicon (Si 4+ ) and trivalent aluminium (Al 3+ ) in the crystalline structure with a divalent metal, such as magnesium (Mg 2+ ), and this leads to a negative surface charge. The ideal unit cell formula of montmorillonite is: {(OH) 4 Montmorillonite particles can be represented as infinitely extended platy particles, also called platelets or lamellae. The half distance, b, between the montmorillonite particles can be estimated from the total void ratio, e. Norrish [1] showed that bentonite can have a dispersed structure or fabric in which clay particles are present as well separated units, or an aggregated structure that consists of packets of particles, or tactoids, within which several clay platelets are in a parallel array, with a characteristic interparticle distance of 0.9 nm.…”
Section: Bentonite Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Isomorphic substitution in montmorillonite usually results in the replacement of a portion of tetravalent silicon (Si 4+ ) and trivalent aluminium (Al 3+ ) in the crystalline structure with a divalent metal, such as magnesium (Mg 2+ ), and this leads to a negative surface charge. The ideal unit cell formula of montmorillonite is: {(OH) 4 Montmorillonite particles can be represented as infinitely extended platy particles, also called platelets or lamellae. The half distance, b, between the montmorillonite particles can be estimated from the total void ratio, e. Norrish [1] showed that bentonite can have a dispersed structure or fabric in which clay particles are present as well separated units, or an aggregated structure that consists of packets of particles, or tactoids, within which several clay platelets are in a parallel array, with a characteristic interparticle distance of 0.9 nm.…”
Section: Bentonite Structurementioning
confidence: 99%
“…Guyonnet et al [4], through a comparison of the results of hydraulic conductivity tests and microscopic analyses of bentonite structure based on small angle X-ray scattering and transmission electron microscopy, showed that high values of the hydraulic conductivity are related to an aggregated fabric (also called the hydrated-solid phase), while low values of the hydraulic conductivity are related to a dispersed fabric (also called the gel phase). These experimental results can be explained by the increase in the average micro-pore size, due to tactoid formation as discussed subsequently in this paper.…”
Section: Bentonite Structurementioning
confidence: 99%
“…s -1 ), were determined under a 100-kPa total confining stress with an oedopermeameter in accordance with the procedures described in NF P 84-705 (AFNOR, 2008) and an apparatus as described in Fig. 1 of Norotte et al (2004) and Guyonnet et al (2005). Tests began with a saturation phase, under 10-kPa, using a 1-mM NaCl solution under a zero hydraulic head.…”
Section: Oedopermeameter Testsmentioning
confidence: 99%
“…Numerous laboratory studies have focused on quantifying the hydraulic conductivity of GCLs in contact with various types of permeant liquids containing cations (Alther et al, 1985;Shan and Daniel, 1991;Egloffstein, 1997;Petrov and Rowe, 1997; Petrov et al, 1997 a,b;Quaranta et al, 1997;Ruhl and Daniel, 1997;Shackelford et al, 2000;Egloffstein, 2001;Jo et al, 2001;Vasko et al, 2001;Ashmawy et al, 2002;Shan and Lai, 2002; Kolstad et al, 2004a,b;Lee et al, 2005;Guyonnet et al, 2005;Jo et al, 2005;Benson et al, 2008; Katsumi et al, 2008a,b;Rauen et al, 2008;Touze Foltz et al, 2008;Guyonnet et al, 2009;Johns and Shamrock 2009;Shackelford et al 2010). Hydraulic conductivity tests were conducted either with flexible wall permeameters (ASTM, 2008(ASTM, , 2003 or rigid-wall permeameters such as the oedopermeameters according to NF P 84-705 (AFNOR, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, factors that affect the fraction of bound water directly affect the hydraulic conductivity of bentonite (Wijeyesekera et al, 2012;Shackelford et al, 2000;Mesri and Olsen, 1971;McNeal et al, 1966). Various studies have shown that the hydraulic conductivity of GCLs can be affected between a factor of 10 and 10,000 when permeated with inorganic permeant solutions (Liu et al, 2015;Scalia et al, 2014;Shackelford et al, 2014;2000;Hosney and Rowe, 2013;Mazzieri et al, 2013;Zhu et al, 2013;Benson et al, 2010;Brown and Shackelford, 2007;Katsumi et al, 2007;Jo et al, 2004;2001;Lee and Shackelford, 2005;Guyonnet et al, 2005;Kolstad et al, 2004;Egloffstein, 2001;Jo et al, 2001;Petrov and Rowe, 1997).…”
Section: Introductionmentioning
confidence: 99%